Analysis of the Impact of the 7p Marketing Mix on Patient Loyalty with the Moderating Variable of Hospital Brand Image (A Study at Anna Hospital and Anna Medika Hospital, Bekasi) - Sri Rahayu Iriani; Sparta Sparta (Publikasi Indonesia, 2026)
The transformation of the global healthcare sector has undergone a significant paradigm shift, where hospitals are no longer perceived solely as social institutions but also as business entities that must remain competitive in an increasingly intense market environment. Private hospitals are required not only to focus on clinical quality but also to implement effective marketing strategies capable of building sustainable patient loyalty. According to global health surveys, approximately 40%–60% of patients tend to switch to other hospitals, highlighting the importance of patient loyalty as a key determinant of business sustainability through quality service delivery. This study aims to analyze the effect of the 7P Marketing Mix (Product, Price, Place, Promotion, People, Process, and Physical Evidence) on patient loyalty, with Brand Image serving as a moderating variable at RS Anna and RS Anna Medika, Bekasi. A quantitative approach was employed using a survey method involving 155 inpatient and outpatient respondents covered by BPJS, insurance, and self-paying schemes. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that, in terms of direct effects, Product, Physical Evidence, and Brand Image have the most significant influence on patient loyalty. Meanwhile, Price, Place, People, Process, and Promotion do not show significant direct effects. Brand Image is proven to function as a moderating variable that strengthens the relationship between marketing mix elements and patient loyalty, particularly within the People dimension related to interpersonal service quality.